Effects of L-ornithine and L-lysine on alkaloid production from in vitro Stemona sp. - Jessadaporn Ruangsak (2018)
Effects of L-ornithine and L-lysine on 1′, 2′-didehydrostemofoline and stemofoline production from in vitro Stemona sp. were investigated. To enhance the production of these alkaloids, the 8-week old plantlets of Stemona sp. were cultured in liquid VMS medium containing 2 mg/l IBA with various concentrations of L-ornithine and L-lysine; 0, 10, 20, 30 and 50 mg/l for 1, 2, 3, 4, 5 and 6 weeks. Dry roots of 0.2 g from each period extracted with methanol and the solution was filtered and evaporated to get crude extract which was extracted again with dichloromethane (DCM). Two hundred milliliters of the medium from each period were extracted with the same procedure but only DCM was used. Finally, Root and medium extracts were analyzed quantitative by high performance liquid chromatography and the total 1′, 2′-didehydrostemofoline and stemofoline production in both root and medium extracts were determined. It was found that when cultured in liquid VMS medium supplemented with 10 mg/l L-ornithine for 5 weeks, Stemona sp. produced the highest total 12, 22-didehydrostemofoline (52.16±5.86 ng/g DW) and highest stemofoline (197.55±10.25 ng/g DW) when cultured in liquid V2MS medium supplemented with 5 mg/l L-ornithine for 6 weeks. Moreover, it was found that when cultured in liquid VMS medium supplemented with 20 mg/l L-lysine for 1 week. Stemona sp. produced the highest total 12, 22-didehydrostemofoline (48.86±1.13 ng/g DW) and stemofoline (168.86±6.13 ng/ g DW).